Arresting Neglect of Learner Studies: Experimentation with Monitoring and Evaluation processes of three secondary schools in Limpopo Province, South Africa - Ngwako Solomon Modiba (Journal of Education and Learning Technology)
This paper evaluates why the bulk of public secondary school learners neglect their studies, despite hating grade repetition. The paper resulted from diverse discourses some of which categorise current pupils to be lazy to be studious despite their uncontrollable desire for success in life. This paper is conceptual and empirical in nature within the qualitative research paradigm. Interviewing techniques and document review were employed to collect data. Out of the population of 16 secondary schools in one of the circuits in the Sekhukhune district in Limpopo Province, South Africa, three were conveniently sampled. In each of the secondary schools, a science education specialist or head of department, a teacher serving in the School Governing Body and a Chairperson of the Representative Council of Learners, became research participants. Findings revealed that firstly, monitoring and evaluation could be a nucleus of learner transformation. Secondly, monitoring and evaluation could promote learner accountability. Thirdly, monitoring and evaluation could identify the specific needs of pupils. Fourthly, the number of teaching periods could compromise monitoring and evaluation. Fifthly, monitoring and evaluation experience resentment in South African schooling. Lastly, low educational outcomes in South African schooling, are ascribed to the absence of monitoring and evaluation. The researcher recommends a culture of monitoring and evaluation in the public education sector. Furthermore, schools need to be guided by management plans to professionalise the monitoring and evaluation processes. The findings of this paper add to the body of knowledge and literature as regards how the judicious application of monitoring and evaluation in secondary schools could restore the missing element of learner accountability to their own studies.